IMPLEMENTASI KERANGKA TPACK MELALUI MEDIA PEMBELAJARAN BERBASIS CANVA BAGI GURU DI SMK NEGERI 2 MEULABOH - Nursiah Nursiah; Uci Mahlisa (Jurnal Genta Mulia, 2025)
One of the problems faced by teachers at SMK Negeri 2 Meulaboh is that they are hampered by choosing learning media that is integrated with technology. Therefore, it is necessary to choose the right application that is easy to use with maximum results. One media that is suitable for delivering interesting teaching material is using Canva media. Researchers consider this application training to be very important to help teachers create interesting learning media. The results of interviews with several teachers at SMK Negeri 2 Meulaboh showed that the use of Canva media as a learning medium has not been carried out optimally and the use of Canva media as an educational tool is still rarely done. The solution that can be given to solve this problem is to provide a learning workshop using Canva to support the implementation of TPACK. The activities carried out include workshops and teacher assistance in making learning media. From the results of the activities, it can be concluded that the implementation of workshops and teacher assistance can provide new knowledge and skills for teachers in creating learning media using Canva. As well as producing a positive response to the way training and mentoring are implemented.